Dietary fats and mortality among patients with type 2 diabetes: analysis in two population based cohort studies - Jiao, Jingjing (BMJ, 2019)
OBJECTIVE: To assess the association of dietary fatty acids with cardiovascular disease mortality and total mortality among patients with type 2 diabetes. DESIGN: Prospective, longitudinal cohort study. SETTING: Health professionals in the United States. PARTICIPANTS: 11 264 participants with type 2 diabetes in the Nurses’ Health Study (1980-2014) and Health Professionals Follow-Up Study (1986-2014). EXPOSURES: Dietary fat intake assessed using validated food frequency questionnaires and updated every two to four years. MAIN OUTCOME MEASURE: Total and cardiovascular disease mortality during follow-up. RESULTS: During follow-up, 2502 deaths including 646 deaths due to cardiovascular disease were documented. After multivariate adjustment, intake of polyunsaturated fatty acids (PUFAs) was associated with a lower cardiovascular disease mortality, compared with total carbohydrates: hazard ratios comparing the highest with the lowest quarter were 0.76 (95% confidence interval 0.58 to 0.99; P for trend=0.03) for total PUFAs, 0.69 (0.52 to 0.90; P=0.007) for marine n-3 PUFAs, 1.13 (0.85 to 1.51) for α-linolenic acid, and 0.75 (0.56 to 1.01) for linoleic acid. Inverse associations with total mortality were also observed for intakes of total PUFAs, n-3 PUFAs, and linoleic acid, whereas monounsaturated fatty acids of animal, but not plant, origin were associated with a higher total mortality. In models that examined the theoretical effects of substituting PUFAs for other fats, isocalorically replacing 2% of energy from saturated fatty acids with total PUFAs or linoleic acid was associated with 13% (hazard ratio 0.87, 0.77 to 0.99) or 15% (0.85, 0.73 to 0.99) lower cardiovascular disease mortality, respectively. A 2% replacement of energy from saturated fatty acids with total PUFAs was associated with 12% (hazard ratio 0.88, 0.83 to 0.94) lower total mortality. CONCLUSIONS: In patients with type 2 diabetes, higher intake of PUFAs, in comparison with carbohydrates or saturated fatty acids, is associated with lower total mortality and cardiovascular disease mortality. These findings highlight the important role of quality of dietary fat in the prevention of cardiovascular disease and total mortality among adults with type 2 diabetes.